2015
DOI: 10.1002/2014pa002714
|View full text |Cite
|
Sign up to set email alerts
|

Persistent millennial‐scale climate variability in the eastern tropical North Pacific over the last two glacial cycles

Abstract: High-resolution sediment records from the eastern tropical North Pacific (ETNP) spanning the last~240 ka B.P. were studied to document the nature of millennial-scale climatic events in the tropical Pacific and to investigate teleconnection mechanisms. We present organic carbon (%OC) and diffuse spectral reflectivity records as indicative of upwelling and productivity changes off NW Mexico over the middle to late Pleistocene. The new productivity records document the persistence of abrupt millennial-scale chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
(197 reference statements)
0
5
0
Order By: Relevance
“…In addition, previous studies in the NE Pacific suggest that during the deglacial and early‐Holocene, the vicinities of the NW Mexican margin received a reduced input of silicates (SiO 2 ), thus limiting diatoms below other producers (Arellano‐Torres et al, ; Pichevin et al, , ). In this scenario, coccolithophores could be more competitive and flourish over diatoms even though suitable amounts of nitrate (NO 3 − ) were present as a consequence of reduced water column denitrification (Arellano‐Torres et al, ; Ganeshram, ; Ganeshram et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies in the NE Pacific suggest that during the deglacial and early‐Holocene, the vicinities of the NW Mexican margin received a reduced input of silicates (SiO 2 ), thus limiting diatoms below other producers (Arellano‐Torres et al, ; Pichevin et al, , ). In this scenario, coccolithophores could be more competitive and flourish over diatoms even though suitable amounts of nitrate (NO 3 − ) were present as a consequence of reduced water column denitrification (Arellano‐Torres et al, ; Ganeshram, ; Ganeshram et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Suitable environmental conditions became optimum for diatoms when silicate became less limited in the vicinities of the NE Pacific due to the upwelling intensification (Addison et al, ; Arellano‐Torres et al, ). The intensification of the upwelling regime favors the nutrient content in the euphotic zone, drives denitrification, and consumes nitrate in subsurface waters through degradation of organic carbon (Arellano‐Torres et al, ; Ganeshram, ; Ganeshram et al, ). However, NO 3 − decline does not limit diatoms as much as silicate, because diatoms are more competitive to store nutrients in vacuoles or storage organelles, among other adaptations (Mock & Medlin, ; Tréguer et al, ; Uitz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Millennial-scale climate changes over the several recent ice-age cycles have been documented in records of deep-sea sediments (e.g., ref. 1 ), Antarctic ice cores 2 3 and Chinese speleothems 4 5 . Several studies on the link between millennial-scale events and ice-age Terminations 4 6 have suggested that these events may play an active role in driving the deglaciation.…”
mentioning
confidence: 99%
“…This observation indicates that terminations could be considered as super-giant events 32 , during which the millennial events and a series of positive oceanic/atmospheric feedbacks 4 played an important role in crossing the threshold. Given the worldwide emergence of remarkable similar millennial-scale records over the last two glacial-interglacial cycles, the pacing of this climate variability may represent a natural resonance in the climate system 1 . The AM transports huge amount of heat and moisture from northern Australia across the Indian and Pacific Ocean to the Asian continent during boreal summer.…”
mentioning
confidence: 99%
“…Concerning the Eastern North Pacific (ENP) OMZ, cores MD02-2507, MD02-2508, MD02-2519, MD02-2521C2, MD02-2525C2, and MD02-2529 were retrieved during the R/V Marion-Dufresne MD126 MONA (IMAGES VII) campaign in 2002 (Blanchet et al, 2007). Age model of these cores were respectively published in Cartapanis et al (2014), Arellano-Torres et al (2015), and Leduc et al (2007Leduc et al ( , 2010.…”
Section: Methodsmentioning
confidence: 99%